2004
DOI: 10.1063/1.1836880
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic metal-base transistor with organic emitter

Abstract: We have fabricated a magnetic metal-base transistor using particularly simple processes. The emitter is organic, consisting of evaporated C60 or tris(8-hydroxiquinoline) aluminum, the base is an electrochemically deposited Co∕Cu∕Co multilayer, and the collector is the n-Si substrate. The collector current measured in the common-base configuration increases significantly in the presence of an applied field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…In the case of common‐base device operation at constant emitter/base junction forward bias, the hybrid spin‐valve 2 and the p‐Si/Sn/PDO27FV/Al are expected to operate due to different processes. In the spin‐valve transistor, the collector current is magnetically modulated due to the different base‐transport factor originated by the spin‐valve‐base that presents a magnetic field dependent charge carrier scattering behaviour.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of common‐base device operation at constant emitter/base junction forward bias, the hybrid spin‐valve 2 and the p‐Si/Sn/PDO27FV/Al are expected to operate due to different processes. In the spin‐valve transistor, the collector current is magnetically modulated due to the different base‐transport factor originated by the spin‐valve‐base that presents a magnetic field dependent charge carrier scattering behaviour.…”
Section: Resultsmentioning
confidence: 99%
“…The incorporation of molecular semiconductors to semiconductor–metal–semiconductor (SMS) transistors 1–3 simplified the technology required to device production and more importantly, allowed the production of devices in vertical architecture with quasi‐ideal common‐base current gains, eliminating the problems that have plagued them for a long time 4. This architecture also reduces device lateral dimensions, allowing again three‐dimensional organization of devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanism of hotelectron injection (a forward-biased emitter Schottky barrier) and hot-electron collection (using another Schottky barrier with a lower barrier height) requires a semiconductor-metalsemiconductor (SMS) structure. Because growing crystalline Si with low defect density on a metal surface is hardly practical [3], metal-film wafer bonding [4] and also as an emitter in a three-terminal device [6], but this lacked an obvious spin-valve effect. Zinc oxide (ZnO), a direct-bandgap oxide semiconductor with bandgap E g = 3.37 eV, forms high-quality Schottky barriers [7], [8] that can be used to generate hot electrons in forward bias, even when deposited as an amorphous film by sputtering.…”
Section: Introductionmentioning
confidence: 99%
“…Bergenti et al have reported that spin polarized materials can successfully replace conventional electrodes in organic light emitting diodes (OLEDs) [9]. Recently, Meruvia et al have produced TFTs by evaporating C 60 as the emitter in magnetic metal-based transistors [10]. Although organic spintronic devices, associating organic semiconductors and magnetic materials, have been investigated by several researchers [8][9][10][11], there have been fewer attempts to understand the mechanism of these devices.…”
Section: Introductionmentioning
confidence: 99%